2022
DOI: 10.1039/d2cc00027j
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of cyclic α-aminoboronates via copper-catalyzed dearomative borylation of 4-quinolinols

Abstract: A highly enantioselective and regioselective dearomative borylation of 4-quinolinols was developed using Cu(I)/(R,R)-Ph-BPE catalyst for efficient synthesis of unprecedented heterocyclic α-amino boronates, a new class of compounds potentially relevant to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Very recently, Li and co-workers reported a regio- and enantioselective copper-catalyzed dearomative borylation of 4-quinolinols 21 , 37 obtained through N -selective Boc-protection of 4-hydroxiquinolines 20 ( Scheme 8 ). Treatment of a variety of N -Boc protected 4-quinolones 21 , with bis(pinacolato)diboron in the presence of CuCl as the catalyst, ( R , R )-Ph-BPE as a chiral ligand, t -BuONa as a base, and MeOH as the proton source, led to cyclic α-aminoboronates 22 in good yields with excellent enantioselectivities.…”
Section: Hydroboration Hydrosilylation and Reduction Reactionsmentioning
confidence: 99%
“…Very recently, Li and co-workers reported a regio- and enantioselective copper-catalyzed dearomative borylation of 4-quinolinols 21 , 37 obtained through N -selective Boc-protection of 4-hydroxiquinolines 20 ( Scheme 8 ). Treatment of a variety of N -Boc protected 4-quinolones 21 , with bis(pinacolato)diboron in the presence of CuCl as the catalyst, ( R , R )-Ph-BPE as a chiral ligand, t -BuONa as a base, and MeOH as the proton source, led to cyclic α-aminoboronates 22 in good yields with excellent enantioselectivities.…”
Section: Hydroboration Hydrosilylation and Reduction Reactionsmentioning
confidence: 99%
“…65 As another example, Li et al reported the hydroboration of 4-quinolinols to give the corresponding bboryl compound without hydrolysis (Scheme 13d). 66 In addition to the commonly used copper catalysis, recent reports also involve some examples of cobalt catalysis. In 2022, Zhao et al reported a Co-catalyzed enantioselective hydroboration of silica-substituted alkenes.…”
Section: Borationmentioning
confidence: 99%
“…65 As another example, Li et al reported the hydroboration of 4-quinolinols to give the corresponding β-boryl compound without hydrolysis (Scheme 13d). 66…”
Section: Reactionsmentioning
confidence: 99%
“…In recent years, copper-catalyzed conjugate addition reactions [ 32 ] of boron have emerged as a viable method to construct borylated heterocycles [ 33 , 34 ]. Among them, the dearomative borylation strategy of indoles [ 35 , 36 , 37 ], pyrroles [ 37 , 38 ], pyridines [ 39 ], and 4-quinolinols [ 40 ] have been efficiently utilized to construct borylated analogs of these biologically significant frameworks. Conjugate borylation of substituted esters and ketones has also been studied, which has demonstrated various challenges in the efficient conversion into corresponding borylated products [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%